Lipase-catalyzed synthesis of chiral poly(ester amide)s with an alternating sequence of hydroxy acid and l/d-aspartate units. Issue 12 (9th March 2018) - Liang, Yiru; Zhang, Yu; Hu, Yujing; Xia, Bo; Lin, Xianfu; Wu, Qi
Abstract : Alternating poly(hydroxyhexanoic acid- alt -l /d -β-aspartate)s with α-benzyl or α-methyl ester side groups were prepared via the enzymatic polycondensation of N -(6-hydroxyhexanoyl)l /d -aspartate diesters. Abstract : Most of reported synthesis approaches for poly(ester amide)s suffer from the difficulty in controlling the sequence of amino acid and ester units, and also some environmental disadvantages. Herein, we developed a facile approach for the lipase-catalyzed synthesis of chirall -/d -Asp-based poly(ester amide)s with alternating aspartate and hydroxyhexanoic acid (HA) units. In the Novozym 435-catalyzed polycondensation starting from four monomers, namely N -(6-hydroxyhexanoyl) aspartate diesters with anl - ord -aspartate configuration, and methyl or benzyl ester groups at the α or β-carbonyl positions of Asp, we successfully obtained the corresponding alternating poly(HA- alt -l /d -β-aspartate)s with α-benzyl or α-methyl ester groups. Thel -aspartate diester monomer was preferred to thed -aspartate diester monomer in the Novozym 435-catalyzed polycondensation, and it also showed high regioselectivity, mainly forming the β-linkage of the aspartate unit. Among the four poly(ester amide)s, poly(HA- alt -l -α-benzyl-β-aspartate) has the highest molar mass of up to 13 000 Da and 98% β-linkage. The thermal properties and the aggregate microstructures of these alternating poly(HA- alt -l /d -aspartate)s were also compared and some interesting differences were observed. Our results also showed that these enantiopure poly(HA- alt -l /d -aspartate)s did not form a stereocomplex.